Assessment of regional asymmetry of the face before and after surgical correction of unilateral cleft lip. Issue 6 (June 2018) - Al-Rudainy, Dhelal; Ju, Xiangyang; Stanton, Steve; Mehendale, Felicity V.; Ayoub, Ashraf
Abstract: This study was carried out on 26 unilateral cleft lip and palate (UCLP) cases with mean age 3.6 ± 0.7 months.3D facial images were captured for each infant 2–3 days before the repair of cleft lip and at 4 months following surgery at a mean age of 8.2 ± 1.8 months, using a stereophotogrammetry imaging system. An iterative closest point (ICP) algorithm was used to superimpose the 3D facial model to its mirror image using VRMesh software. After the superimposition, the face model was divided into seven anatomical regions. Asymmetry of the entire face and of the anatomical regions was calculated by measuring the absolute distances between the 3D facial surface model and its mirror image. Colour maps were used to illustrate the patterns and magnitude of the facial asymmetry before and after surgery. There were significant decreases in the asymmetry scores for the nose, upper lip and the cheeks as a result of the surgical repair of cleft lips. Surgery did not change the magnitude of the asymmetry scores for the lower lip and chin. Residual nasolabial asymmetries were detected. The main outcome of the findings of this innovative study is to inform the required surgical refinement of primary repair of cleft lip in order to minimise facial asymmetry. We have presented a sensitive tool that could be used for comparative analysis of lip repair at various cleft centres and to guide secondary corrective surgery when required.